Studies on Complexes of 1,2-Bis-(8-quinoxy) Ethane with Some Bivalent Metal Ions - Annapoorani, S.; Parmeswaran, V.R. (Asian Journal of Chemistry, 2010)
1,2-Bis-(8-quinoxy) ethane was prepared by refluxing 8-hydroxy quinoline with 1,2-dibromoethane for 22 h. Some complexes were synthesised using this ligand with some bivalent metal ions. The complexes were characterised by elemental analysis, infrared, UV-visible spectra and conductivity measurements.